Is intraoperative parathyroid monitoring during minimally invasive parathyroidectomy still justified? - Hargitai, Lindsay; Boryshchuk, Daniela; Arikan, Melisa; Binter, Teresa; Scheuba, Christian; Riss, Philipp (Frontiers in Endocrinology, 2024)
Introduction: Primary hyperparathyroidism (PHPT) is the third most common endocrine disease. With parathyroidectomy, a cure rate of over 95% at initial surgery is reported. Localization of the abnormal parathyroid gland is critical for the operation to be successful. The aim of this study is to analyze data of patients with single gland disease (SGD) and positive concordant localization imaging undergoing minimally invasive parathyroidectomy (MIP) and intraoperative parathyroid hormone monitoring (IOPTH) to evaluate if IOPTH is still justified in patients with localized SGD. Methods: A retrospective database analysis of all minimally invasive operations with IOPTH for PHPT and positive concordant localization in ultrasound (US) and 99m Tc-sestamibi scintigraphy (MIBI) between 2016-2021. When both US and MIBI were negative, patients underwent either choline or methionine PET-CT. The patients were also analyzed a second time without applying IOPTH. Results: In total, 198 patients were included in the study. The sensitivity of US, MIBI and PET-CT was 96%, 94% and 100%, respectively. Positive predictive value was 88%, 89% and 94% with US, MIBI and PET-CT, respectively. IOPTH was true positive in 185 (93.4%) patients. In 13 (6.6%) patients, no adequate IOPTH decline was observed after localizing and extirpating the assumed enlarged parathyroid gland. Without IOPTH, the cure rate decreased from 195 (98.5%) to 182 (92%) patients and the rate of persisting disease increased from 2 (1.0%) to 15 (7.5%) patients. Conclusion: Discontinuing IOPTH significantly increases the persistence rate by a factor of 7.5 in patients with concordantly localized adenoma. Therefore, IOPTH appears to remain necessary even for this group of patients.